Efficacy and Safety of Controlled Ovarian Stimulation With or Without Letrozole Co-administration for Fertility Preservation: A Systematic Review and Meta-Analysis - Bonardi, Benedetta; Massarotti, Claudia; Bruzzone, Marco; Goldrat, Oranite; Mangili, Giorgia; Anserini, Paola; Spinaci, Stefano; Arecco, Luca; Del Mastro, Lucia; Ceppi, Marcello; Demeestere, Isabelle; Lambertini, Matteo (Frontiers in Oncology, 2020)
Background The co-administration of letrozole during controlled ovarian stimulation (COS) with gonadotropins is used to limit the potentially harmful effects of a supra-physiological rise in estrogen levels on hormone-sensitive cancers. However, the efficacy and safety of adding letrozole to COS remains debated. Methods This is a systematic review and meta-analysis of published studies that compared the efficacy and safety of COS with co-administration of letrozole versus COS without letrozole in all patient populations. A secondary analysis was done including only the studies in breast cancer patients. The primary efficacy endpoint was the number of retrieved mature Metaphase II (MII) oocytes. Secondary efficacy and safety endpoints were total number of oocytes, maturation rate, fertilization rate, number of cryopreserved embryos, peak estradiol levels, progesterone levels, total gonadotropin dose. Data for each endpoint were reported and analyzed thorough mean ratio (MR) with 95% confidence interval (CI). Results A total of 11 records were selected including 2,121 patients (990 patients underwent COS with letrozole and 1,131 COS without letrozole). The addition of letrozole to COS did not have any negative effect on the number of mature oocytes collected (MR=1.00, 95% CI=0.87-1.16; P=0.967) and the other efficacy endpoints. COS with letrozole was associated with significantly decreased peak estradiol levels (MR=0.28, 95% CI=0.24-0.32, P<0.001). Similar results were observed in the secondary analysis including only breast cancer patients. Conclusions These findings are reassuring on the efficacy and safety of COS with gonadotropins and letrozole and are particularly important for fertility preservation in women with hormone-sensitive cancers.